2015
DOI: 10.1177/1362361315580442
|View full text |Cite
|
Sign up to set email alerts
|

Family wellbeing of individuals with autism spectrum disorder: A scoping review

Abstract: Families play an important role in supporting individuals with autism spectrum disorder across the lifespan. Indicators of family wellbeing can help to establish benchmarks for service provision and evaluation; however, a critical first step is a clear understanding of the construct in question. The purpose of the current scoping review was to (a) summarize current conceptualizations and measurements of family wellbeing, (b) synthesize key findings, and (c) highlight gaps and limitations in the extant literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 134 publications
(229 reference statements)
4
56
1
1
Order By: Relevance
“…In addition, three significant confounders were related to adaptation including relationship to child, presence of non-parental adults in the household, and race of caregiver. Other studies have consistently found that mothers have lower levels of well-being and higher levels of distress than fathers [32,33,34,35]. One potential explanation for the surprising finding that biological mothers in our study tended to have higher levels of adaptation is that the mothers in the current study assumed more traditional parental roles, and therefore were less likely to report inability to adapt because it could have been viewed as a reflection on themselves as parents.…”
Section: Discussioncontrasting
confidence: 45%
“…In addition, three significant confounders were related to adaptation including relationship to child, presence of non-parental adults in the household, and race of caregiver. Other studies have consistently found that mothers have lower levels of well-being and higher levels of distress than fathers [32,33,34,35]. One potential explanation for the surprising finding that biological mothers in our study tended to have higher levels of adaptation is that the mothers in the current study assumed more traditional parental roles, and therefore were less likely to report inability to adapt because it could have been viewed as a reflection on themselves as parents.…”
Section: Discussioncontrasting
confidence: 45%
“…In this regard, parents/caregivers play an important role in supporting individuals with ASD across their lifespan. The well‐being of families of individuals with ASD, however, rarely takes center stage in research and policy arenas alike . Much like other societies in transition where older traditions still dominate different rungs of the society, in Oman too, the family is central to the functioning of communities .…”
Section: Discussionmentioning
confidence: 99%
“…The well-being of families of individuals with ASD, however, rarely takes center stage in research and policy arenas alike. 28 Much like other societies in transition where older traditions still dominate different rungs of the society, in Oman too, the family is central to the functioning of communities. 29 And yet, family has been kept in the peripheries of any discussion relevant to caring for children with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the term wellbeing has not been well defined in the broader literature (e.g., Dodge, Daly, Huyton, & Sanders, 2012;Ereaut & Whiting, 2008;Manderson, 2005), or in the ASD research field (e.g., Tint & Weiss, 2016). However, research has increasingly emphasised wellbeing as a multidimensional concept (e.g., Pozo, Sarriá, & Brioso, 2014), which goes beyond simply adapting and returning to baseline.…”
Section: Parental Adaptation and Wellbeingmentioning
confidence: 99%